Occupational Health & Safety Cost Analysis in Civil Construction Projects - Hana Fajrianti; Mila Tejamaya (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Occupational Health and Safety (OHS) costs are crucial for implementing safety management systems in the construction sector, particularly in Indonesia. Previous studies emphasize the potential benefits of effective OHS cost planning in reducing workplace accidents and associated costs. Objective: This study aims to analyze the allocation of OHS costs and its correlation with workplace accidents across various construction projects in Indonesia. Method: A descriptive analysis approach was employed to examine OHS cost allocation and incident rates in ten construction projects conducted by a state-owned company across multiple regions in Indonesia. Data analysis utilized Microsoft Excel and SPSS, with Pearson correlation tests conducted to assess relationships between variables. Result: The study found significant variation in OHS cost allocation, ranging from 0.20% to 1.23% of project value across different projects. Larger projects tended to allocate a lower percentage of their budget to OHS compared to smaller ones. Conclusion: Effective planning of OHS costs is essential not only in terms of percentage allocation but also considering project size, duration, workforce size, and technological aspects. The study underscores the importance of comprehensive cost-benefit analyses to further understand the impact of OHS provision on accident prevention in construction projects.